Antena Vivaldi Konvensional untuk Penerapan pada Radar Cuaca (9.4 GHz) - Randhika Rianza; Uzma Septima; Ahmad Dahlan; Firdaus Firdaus; Nasrul Nasrul; Yulindon Yulindon; Yustini Yustini (Elektron : Jurnal Ilmiah, 2022)
To predict weather conditions as an anticipation act towards natural disasters, a weather radar is needed. In weather radar technology, antennas play an important role in supporting the performance of the weather radar. Vivaldi antenna is the right choice because it has an unlimited bandwidth so it is able to operate at the desired work frequency, including the working frequency of weather radar (9.4 GHz). This research discusses the modification of tapered slots, circular stub, radial stub, length and width of the reference vivaldi antenna [1] using CST Studio software. After modifications and measurements, a return loss value of -23.25336989 dB, bandwidth of 500 MHz, VSWR 1.188463357, gain of 3.99 dBi, and unidirectional radiation patterns. All the resulting antenna parameter values are in good condition and qualify the weather radar antenna for a working frequency of 9.4 GHz.